2012
DOI: 10.1093/cercor/bhs147
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interneuron Networks in Driving Human Motor Cortical Plasticity

Abstract: The after-effects of repetitive transcranial magnetic stimulation (rTMS) are highly variable between individuals. Because different populations of cortical neurons are stimulated more easily or are more excitable in different people at different times, the variability may not be due to differences between individuals in the plasticity of cortical synapses, but may instead be due to individual differences in the recruitment of cortical neurons. In this study, we examined the effects of rTMS in 56 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

80
748
11
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(889 citation statements)
references
References 68 publications
80
748
11
6
Order By: Relevance
“…While the neuromodulatory after-effects induced by NIBS techniques (including tDCS) appear to be relatively stable over prolonged time courses (López-Alonso et al, 2015), the nature and magnitude of these effects varies considerably between individuals (Hamada, Murase, Hasan, Balaratnam, & Rothwell, 2013;Nettekoven et al, 2015;Nitsche & Paulus, 2001;Wiethoff, Hamada, & Rothwell, 2014). One source of this variability may be the brain statedependent nature of these effects, meaning that the history of endogenous activity of one region may be crucial to the effects of brain stimulation (Silvanto, Cattaneo, Battelli, & Pascual-Leone, 2008) and consequent activation of homeostatic and non-homeostatic metaplasticity mechanisms (Amadi et al, 2015;Muller-Dahlhaus & Ziemann, 2015).…”
Section: Caveats and Considerations For The Futurementioning
confidence: 99%
“…While the neuromodulatory after-effects induced by NIBS techniques (including tDCS) appear to be relatively stable over prolonged time courses (López-Alonso et al, 2015), the nature and magnitude of these effects varies considerably between individuals (Hamada, Murase, Hasan, Balaratnam, & Rothwell, 2013;Nettekoven et al, 2015;Nitsche & Paulus, 2001;Wiethoff, Hamada, & Rothwell, 2014). One source of this variability may be the brain statedependent nature of these effects, meaning that the history of endogenous activity of one region may be crucial to the effects of brain stimulation (Silvanto, Cattaneo, Battelli, & Pascual-Leone, 2008) and consequent activation of homeostatic and non-homeostatic metaplasticity mechanisms (Amadi et al, 2015;Muller-Dahlhaus & Ziemann, 2015).…”
Section: Caveats and Considerations For The Futurementioning
confidence: 99%
“…4b). Recently, Chew the expected facilitation after iTBS (Hamada et al 2013). Although speculative, it is not only 608 conceivable that the inter-individual variability we observed in our study is at least in part 609 due to differences in I wave recruitment between individuals but also that the intra-subject 610 variability in response to the different types of stimulation (atDCS vs. iTBS) can be explained 611 to some extent by differences in the physiological underpinnings of their after-effects.…”
mentioning
confidence: 99%
“…Unfortunately, the induction of plastic changes with non-invasive brain stimulation is currently variable and unreliable (Hamada, Murase, Hasan, Balaratnam, & Rothwell, 2013;Ridding & Ziemann, 2010;Sale, Ridding, & Nordstrom, 2007b). There are several factors that have already been identified that seem to contribute to the variability of induced effects (for review see Ridding & Ziemann, 2010), including genetics (Witte et al, 2012), age (Todd, Kimber, Ridding, & Semmler, 2010), history of previous cortical activity (Sale & Mattingley, 2013), time of day of stimulation (Sale et al, 2007b(Sale et al, , 2008, and cognitive factors such as attention (Kamke, Hall, et al, 2012;Kamke et al, 2014).…”
Section: Discussionmentioning
confidence: 99%